A quicker route to hydrogen economy with ammonia - Erdemir, Dogan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The urgent need for decarbonization drives the exploration of clean energy sources and carbon-free fuels, primarily with hydrogen as an emerging solution. This short communication article aims to provide a unique perspective on how to expedite transition to the hydrogen economy and make a quicker route to sectoral hydrogen-based solutions by deploying ammonia. The primary goal is, in this regard, to utilize green hydrogen as a clean feedstock and directly switch to synthesise ammonia for using it in almost all sectors directly without making infrastructural changes for hydrogen storage, transportation and distribution. This is due to the fact that the ammonia ecosystem already exists, but depending essentially on unclean hydrogen where fossil fuels are deployed to produce it. So, using the existing ammonia ecosystem with clean hydrogen production should be a target to overcome numerous challenges, especially requiring more investments and infrastructural changes. Furthermore, clean ammonia is potentially used as a fuel, an energy carrier, a working fluid, a refrigerant, and a commodity for various sectors, including industrial and agricultural.
Keywords: Ammonia; Hydrogen economy; Ammonia fuel cells; Carbon-free fuel; Sustainability; Ammonia energy technologies; Chemistry; Electrochemistry; Energy & Fuels